ALA Library Schools and Subject Reference Coursework: A Short Communication - Condic, Kristine (Journal of education for library and information science, 2016)
Reference librarians are exposed to the literature of different disciplines in a number of ways including advanced degrees, on the job training, and intellectual inquisitiveness. As students, many reference librarians were also exposed to library science programs offering coursework specializing in information sources and research within other disciplines. A brief study of current library science programs in the United States reveals that approximately half of these programs offer specialized reference coursework in the humanities, social sciences, and sciences. Comparing these results to a previous study, one finds that humanities and social sciences courses have proportionately diminished while medical and health sciences courses have increased. These changes have implications for LIS educators preparing students for reference work.